(untitled) (Conferencea, 2024)
"Strategy for the development of New Uzbekistan in 2022-2026" was adopted in Uzbekistan. To accelerate the economic growth and development of the country, it determines the priority directions of transformations. The strategy of "New Uzbekistan" aims to attract foreign investments in the amount of 70 billion US dollars in five years, and the need to develop and adopt an effective strategy for attracting direct investments is very important [5].